The Prevention of the Renal Chronic Damage: a Priority from Childhood - Aymahara Gómez Morejón; Lidia Rosa Pérez González; Ortelio Chaviano Mendoza; Jan O’neil González Ramos; Juan Carlos Yanes Macías; Annia Quintana Marrero (Revista Finlay)
Background: chronic kidney disease in children has become a serious public health problem, it implies a high risk of mortality that increases over the years, its early recognition allows to act on risk factors and prevent their progression to terminal stages. Objective: to describe the clinical-epidemiological characteristics of chronic kidney disease in children treated at the Paquito González Cueto Cienfuegos Pediatric University Hospital in the period 2018-2020. Methods: a retrospective descriptive study was carried out, a series of cases in patients diagnosed with chronic kidney disease in the last 3 years, with a universe of 260 patients. Clinical and epidemiological variables were analyzed. For the analysis of the results, the SPSS 15.0 program was used, which allowed the processing, statistical analysis and preparation of the output tables. Results: 260 patients with chronic kidney disease were treated. The male sex was the most affected (59.2 %); the age group that predominated was that of 5 to 14 years (43.9 %); 92.3 % of the patients were found in stage I of the disease; the most associated risk factor and the most frequent causes were congenital malformations (75 %), being vesico-ureteral reflux the one that affected a greater number of patients (53.3 %); 61.8 % of the patients with glomerulopathies had minimal damage disease 42,6 % were asymptomatic. Conclusions: chronic kidney disease is one of the main causes of morbidity and mortality that has been increasing in recent years in pediatric age, with congenital malformations of the genitourinary system being its main cause; early detection of risk prevents its progression.